Assessing students' 'clean and healthy living behavior' in an intervention program - Henny Endah Anggraeni; Yudith Vega Paramitadevi; Fany Apriliani; Ika Resmeiliana (International Journal of Public Health Science (IJPHS), 2023)
The Indonesian government manages the health and environment of students through the post-Islamic boarding school program. However, it has not run optimally due to students' lack of knowledge and literacy on personal and environmental sanitation. This study identified the knowledge about an environmental-based sanitation approach among students at boarding schools. The study was conducted in October 2021 using the principle of the pre-post test method based on an intervention study. The students who participated in this study were 70 female students of Junior and Senior High School levels. The students were given practical training regarding the concept and benefits of 'clean and healthy living behavior' (CHLB), infectious skin diseases, the status of waste management, and health and environmental issues resulting from burning waste. The statistical analysis uses Chi-square descriptive analysis. There was an increase in the post-test results compared to the pre-test by 5% for students' understanding of the definition of CHLB and 60% for students' understanding of air pollution reduction efforts from the students' point of view. The students understand learning environment-based sanitation through practical intervention.